Strategic instability in Korea - Loo, Bernard Fook Weng (2011)
The Korean Peninsula remains one of the most dangerous hotspots in the Asia Pacific. With the emergence of a new and unknown North Korean leader - and if wise heads do not prevail in either Seoul or Pyongyang -the region may be on the brink of renewed hostilities.